Strengthen detection of raw milk somatic cell count - the first step for China milk quality improvement - Shidong Zhang (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Milk is a healthy natural beverage and the main raw material of dairy products. It is well known that raw milk is the first link to guarantee and control the quality and safety of milk and dairy products. Only high-quality raw milk can produce high-quality dairy products.